PATHOGENIC EFFECTS ASSOCIATED WITH TRYPANOSOMA DANILEWSKYI STRAIN FCC 1 INFECTION IN JUVENILE COMMON CARP, CYPRINUS CARPIO L - M. S. Ahmed; K. Shafiq; H. Ali; F. Ollevier (Journal of Animal and Plant Sciences, 2011)
Mortality and pathological effects caused by Trypanosoma danilewskyi strain F Cc 1 in laboratory-infected single breed juvenile common carp were investigated in this study. The study was divided into two parts. In the first part, four groups (A-D) each containing 20 fish (4 months old) were inoculated intraperitoneally with various size of inocula; 1000, 25,000 and 50,000 live trypanosomes/fish in groups A-C respectively while group D was injected 0.2 ml of PSG (phosphate buffered saline with glucose, pH 7, filter sterilized)/fish as a control. Blood was examined at 10 days intervals to monitor the development of parasitemia. All dead fish were counted and their blood and body fluids were examined for the presence of trypanosomes. The second part of the study was conducted under the similar conditions as first part to measure the pathological effects induced by the infection of T. danilewskyi strain FCc 1. Two groups, (A & B) each containing 40 fish (5 months old) were inoculated with 50,000 live trypanosomes/fish in group A and 0.2 ml PSG/fish in group B (control). Blood was examined at 10 days intervals and used for the estimation of parasitemia, hematocrit, hemoglobin and thin blood smear preparations. In the first part of study no fish died in groups A & D, 12.5 % mortality was observed in group B and 50 % in group C. The second part revealed a significant decrease in hematocrit, hemoglobin, erythrocyte counts and significant increase in leukocytes counts was observed in infected fish (group A) when compared to the control (group B) at the same interval of time.  Thus it is concluded that Trypanosoma danilewskyi strain F Cc 1 is a potential hemoflagellate pathogen of juvenile common carp as it causes mortality, anemia and altered blood parameters.
Keywords: pathogenic effects; T. danilewskyi strain FCc 1; hemoglobin; leukocytes; carp; mortality.